Temporal trends in vaccination coverage in the first year of life in Brazil - Ana Beatriz Batista Neves; Lucas Emanuel de Oliveira Silva; Gabriela Morais Celestino Amaral; Maria Rosa da Silva; Claudio José dos Santos Júnior (Sociedade de Pediatria de São Paulo, 2023)
ABSTRACT Objective: The aim of this study was to analyze the temporal trends in vaccination coverage (VC) during the first year of life of children in Brazil. Methods: Data on VC for the first year of life from 2011 to 2020 for Bacille Calmette-Guerin (BCG), hepatitis B, polio, pentavalent, and triple viral vaccines at the national, regional, and state levels were obtained from the Information System of the National Immunization Program. Trends were analyzed using Prais-Winsten generalized linear regression models and average annual percent change (APC) estimates. Results: Decreasing trends were observed for the BCG (APC −3.58%; p<0.05), pentavalent (APC −4.10%; p<0.05), polio (APC −2.76%; p<0.05), and triple viral (APC −2.56%; p<0.05) vaccines in the country. Hepatitis B vaccine was the only vaccine that displayed stationary behavior (APC −4.22%; p>0.05). During the study period, no increasing trends were observed in any territory or vaccine. Conclusions: This study shows a recent significant reduction and decreasing trends in VC during the first year of life of children in Brazil, indicating the need for interventions to curb this ongoing phenomenon and to recover acceptable VC rates in the country.